Spatial variability of Soil fertility using soil chemical data, Atrush area, Duhok, Kurdistan region, Iraq - I, Lida; Taher, Sipal M.; Barwari, Vahil I. H.; Rekani, Omar A. O. (Sulaimani Journal for Pure and Applied Sciences, 2016)
One of the basic factors in sustainable crop production is enhancing soil quality based on the soil fertility and returning absorbed nutrition by plants to the soil. In this spatial research variability of soil properties in Atrush area in Duhok province, Iraq was conducted based on the 15 soil samples with randomized method were taken from different locations. Statistical analysis by SPSS and spatial distribution and interpolation of soil properties by GS+softwarewas done. Results showed all studied soil parameters such as pH, EC, %OM, percent of sand, silt and clay, %total N, available P and K hadanormal distribution. Strong spatial dependence related tothepercent of organic matter, sand and clay percent, percent of total nitrogen, available phosphorus and potassium while pH, EC, and percent of silt showed moderate spatial dependence. The variogram model were spherical for pH, EC, %OM, %clay and % total nitrogen while for sand percent and available P were linear and for available K and percent of silt were exponential. Spatial interpolation accuracy and precision by MAE, MBE and RMSE showedKriging prediction maps for pH, EC, %OM, %N, and available K had most accurate predictions with the lowest error, therefore, it can provide useful information about urban planning and environmental management.
Keywords: Geostatistics; Semivariogram; Soil properties; spatial variability